LANGUAGE AND ATTITUDE - Rafika Dewi Nasution (VISION, 2017)
This article deals with Sociolinguistics, and focus on Language and Attitude,  and includes  about Theory of Attitude in Language, Language Attitude and Language Learning, and Application of Sociolinguistics.